The Silent Struggle for Self-Discovery: Patriarchy and Feminine Identity in Shashi Deshpande’s That Long Silence - Yadav, Shalini (Feminist theology, 2026)
This paper delves into the inner struggle of Jaya, the central female character in Shashi Deshpande?s That Long Silence, as she navigates her roles as a wife, mother and individual in a patriarchal society. It explores the deep-seated gender inequalities and societal pressures that force women into silence and submission. Jaya, representing a middle-class, educated housewife, is portrayed as a woman caught between traditional expectations and a desire for self-identity. Deshpande?s portrayal emphasizes not only the limitations imposed by external forces, such as patriarchy, but also the internalized acceptance of these roles by women themselves. The article highlights how Jaya?s journey reflects the broader struggles of Indian women who often sacrifice personal ambitions and desires for the sake of their families, with their lives heavily controlled by their husbands and societal norms. However, Deshpande goes beyond blaming patriarchy alone, suggesting that women?s passive acceptance of their traditional roles contributes to their own subjugation. Through her nuanced and introspective writing, Deshpande uncovers the complex emotions and unconscious thought processes of her female characters, presenting them as sensitive, hesitant, yet intelligent and creative.